A method for preparing a sandwich structure electrode foil

By forming a composite film of SBA-15, cellulose and methylcellulose on the electrode foil of aluminum electrolytic capacitor, the problem of poor hydration resistance of traditional electrode foils is solved, and higher hydration resistance and longer service life are achieved.

CN119361326BActive Publication Date: 2025-03-21NANTONG HAIXING ELECTRONICS +2
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
CN202411960104.7
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-12-30
Publication Date
2025-03-21
Estimated Expiration
2044-12-30

AI Technical Summary

Technical Problem

The electrode foil of traditional aluminum electrolytic capacitors has poor hydration resistance, which affects its service life.

Method used

Using the preparation method of sandwich structure electrode foil, a composite film is formed by mixing SBA-15, cellulose and methyl cellulose, and the adsorption of the molecular sieve and the porous structure are isolated from moisture. The composite film of cellulose and methyl cellulose form a composite film on the surface to further isolate moisture.

Benefits of technology

The hydration resistance of the electrode foil is significantly improved, and through the synergistic action of the molecular sieve and the cellulose composite film, it effectively isolates moisture from contact with the aluminum foil, and extends the service life of the capacitor.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_1
    Figure SMS_1
Patent Text Reader

Abstract

The present invention relates to the technical field of manufacturing electrode foil for aluminum electrolytic capacitors, and specifically to a method for preparing a sandwich structure electrode foil. The method for preparing the sandwich structure electrode foil of the present invention comprises the following steps: preparing a high dielectric constant layer, preparing a powder sintering layer, and preparing an anti-hydration protective layer; the anti-hydration protective layer is obtained by immersing a chemically formed foil in a mixed solution of SBA-15, cellulose, methyl cellulose and N-methylpyrrolidone, and drying. The sandwich structure electrode foil of the present invention successively prepares a high dielectric constant layer, a powder sintering layer, and an anti-hydration protective layer on the surface of a plain foil substrate, and finally obtains an electrode foil with high capacity, long life, and environmentally friendly preparation.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of manufacturing electrode foils of aluminum electrolytic capacitors, and in particular to a method for preparing a sandwich structure electrode foil. Background Art

[0002] With the rise of emerging consumer electronics, such as new energy vehicle on-board electronics, charging piles, and 5G base stations, higher requirements are placed on the comprehensive performance of the electrode foil of aluminum electrolytic capacitors, such as high capacity and environmental protection requirements; the electrode foil for traditional aluminum electrolytic capacitors is mainly increased by electrochemical corrosion. On the one hand, the acid treatment of corrosion has brought certain pressure to the environmental protection. On the other hand, the method of increasing the specific surface area by corrosion has been close to the theoretical limit. Therefore, a new method is to use aluminum powder sintered foil with higher specific surface area by sintering aluminum powder on both sides of the aluminum foil.

[0003] Patent document CN118610004A discloses an aluminum foil capacitor sintered foil and a preparation method thereof, which prepares a slurry with good fluidity by reasonably combining aluminum powder and resin, and then sintering the slurry after coating it on aluminum foil to achieve a metallurgical firm bonding between the aluminum paste and the aluminum foil.

[0004] However, during the use of capacitors, they are highly sensitive to moisture, which directly affects the service life of the capacitors. Therefore, it is urgent to improve the hydration resistance of aluminum foil. Summary of the invention

[0005] In view of this, the purpose of the present invention is to provide a method for preparing a sandwich structure electrode foil to solve the problem that the traditional electrode foil has poor hydration resistance.

[0006] Based on the above purpose, the present invention provides a method for preparing a sandwich structure electrode foil, comprising the following steps:

[0007] S1: dissolving ammonium fluorotitanate in water to obtain an ammonium fluorotitanate solution, then immersing an aluminum foil in the ammonium fluorotitanate solution, taking out the aluminum foil, cleaning it, and then sintering it;

[0008] S2: mixing aluminum powder and an organic solvent to obtain aluminum powder slurry, and coating the aluminum powder slurry on the upper and lower surfaces of the aluminum foil obtained in step S1, and sintering to obtain a sintered foil;

[0009] S3: chemically forming the sintered foil to obtain a chemically formed foil;

[0010] S4: SBA-15, cellulose, methyl cellulose and N-methyl pyrrolidone are mixed to obtain a mixed solution, and then the formed foil is placed in the mixed solution, washed with water, and dried to obtain a sandwich structure electrode foil;

[0011] The amount ratio of SBA-15, cellulose, methyl cellulose and N-methyl pyrrolidone in step S4 is 10-20 g: 9-18 g: 1-2 g: 150-300 ml;

[0012] Preferably, the thickness of the aluminum foil in step S1 is 60-90 μm.

[0013] Preferably, during the immersion in step S1, the temperature of the ammonium fluorotitanate solution is 20-60° C., and the immersion time is 6-10 min.

[0014] Preferably, the usage ratio of ammonium fluorotitanate and water in step S1 is 10-20 g:1000 ml.

[0015] Preferably, the sintering in step S1 is performed in a muffle furnace.

[0016] Preferably, the sintering in step S1 finally obtains a corrosion foil with a high dielectric constant titanium dioxide film with a thickness of 1-3 nm coated on the surface.

[0017] Preferably, the sintering temperature in step S1 is 200-500° C., and the holding time is 3-10 min.

[0018] Preferably, the particle size of the aluminum powder in step S2 is 3-10 μm.

[0019] Preferably, the ratio of the aluminum powder to the organic solvent in step S2 is 10-20 g: 20-40 ml.

[0020] Preferably, the organic solvent in step S2 is one of ethanol, ethylene glycol, acetone, N-methylpyrrolidone, and N,N-dimethylformamide.

[0021] Preferably, the single-side thickness of the coating in step S2 is 10-30 μm.

[0022] Preferably, the specific process of sintering in step S2 is as follows: at 1×10-2Pa, first increase the temperature to 250-350°C at a heating rate of 30-60°C / min, and keep warm for 4-8h, then increase the temperature to 500-650°C at a heating rate of 30-60°C / min, and keep warm for 8-12h.

[0023] Preferably, the chemical formation in step S3 is as follows: the sintered foil is placed in 90-98°C water and boiled for 8-10 minutes; then rinsed with deionized water and drained; then placed in 2%-10% ammonium adipate and 0.5%-2% ammonium citrate at a mass percentage concentration of 70-90°C and a current density of 10-20 mA / cm 2, the primary formation is carried out under the condition of 150V voltage, the formation time is controlled at 10-20min, and it is taken out for washing; it is placed in a solution of ammonium adipate with a mass percentage concentration of 2%-10% and ammonium citrate with a mass percentage concentration of 0.2%-1.5%, and the current density is 10-20mA / cm 2 , 260V, the secondary formation is carried out under the conditions of the formation time is controlled at 10-15 min, and it is taken out for washing; it is placed in azelaic acid with a mass percentage concentration of 4%-15% and sodium hydroxide with a mass percentage concentration of 0.1%-1%, and the current density is 10-20mA / cm 2 , 360V, the three-stage formation is carried out under the conditions of 8-15 min, and the formation time is controlled at 8.5-15 min, and then it is taken out for washing; it is placed in a 4%-15% mass percentage concentration of azelaic acid and a 0.1%-1% mass percentage concentration of sodium hydroxide solution, and the current density is 10-20 mA / cm at 80-95 ° C. 2 The electrode was subjected to four-stage formation at 400V and 20-30min, and then washed with water; the electrode was placed in a boric acid solution having a mass percentage concentration of 10%-12% and an ammonium pentaborate solution having a mass percentage concentration of 1%-1.5%, and the current density was 10-20mA / cm 2 , 520V, the formation time is controlled within 5-10min, and it is taken out for washing; it is immersed in a phosphoric acid solution with a mass percentage concentration of 5%-10%, the temperature is controlled at 50-80℃, the immersion time is controlled within 5-10 min, and it is taken out for washing; the foil obtained in the above step is placed in an oven, the temperature is controlled at 400-550℃, and the time is controlled within 3-5min; it is placed in a boric acid solution with a mass percentage concentration of 4%-15% and an ammonium pentaborate solution with a mass percentage concentration of 0.1%-1%, and the current density is 10-20mA / cm 2 The subsequent formation is carried out under the conditions of 500V and 520V, the formation time is controlled within 5-10 min, and the electrode is taken out for washing.

[0024] Beneficial effects of the present invention:

[0025] The present invention mixes SBA-15, cellulose and methyl cellulose. The adsorption effect of the molecular sieve and the porous structure can isolate a part of the water from contacting the aluminum foil. At the same time, the cellulose and methyl cellulose can form a composite film on the surface thereof, further isolating the penetration of water. The two have a mutual synergistic effect, and together improve the hydration resistance thereof. DETAILED DESCRIPTION

[0026] In order to make the objectives, technical solutions and advantages of the present invention more clearly understood, the present invention is further described in detail below in conjunction with specific embodiments.

[0027] Example 1: A sandwich structure electrode foil, the specific preparation steps are as follows:

[0028] (1) Dissolve 10 g of ammonium fluorotitanate in 1 L of water and stir magnetically for 3 h to obtain an ammonium fluorotitanate solution. Then, immerse a 60 μm thick plain foil substrate in the ammonium fluorotitanate solution and keep it at 20 °C for 6 min. After taking it out, rinse it with deionized water, drain it, and repeat this process 3 times. Then, place it in a muffle furnace at 200 °C for 3 min to obtain a corrosion foil coated with a 2 nm thick high dielectric constant titanium dioxide film.

[0029] (2) Mix 10 g of aluminum powder with a particle size of 3 μm with 20 ml of ethanol and stir magnetically for 10 min to obtain aluminum powder slurry;

[0030] (3) Use a coating machine to evenly coat the aluminum powder slurry on the upper and lower surfaces of the aluminum foil in step (1), then place it in a muffle furnace, turn on the vacuum pump, and evacuate to 1×10 -2 Pa, sintering was performed, first at a heating rate of 30°C / min to 250°C, kept at that temperature for 4 h, then at a heating rate of 30°C / min to 500°C, kept at that temperature for 8 h;

[0031] (4) The aluminum foil obtained in step (3) was placed in 90°C water and boiled for 8 min; then rinsed with deionized water and drained; then placed in 2% by mass concentration of ammonium adipate and 0.5% by mass concentration of ammonium citrate at 70°C and a current density of 10 mA / cm 2 The first stage was formed at a voltage of 150 V for 10 min, and the sample was taken out for washing; the sample was placed in a 2% by mass concentration of ammonium adipate and a 0.2% by mass concentration of ammonium citrate, and the reaction mixture was heated at 70 ° C and a current density of 10 mA / cm 2 The secondary formation was carried out under the conditions of 260V and 10min, and the formation time was controlled at 10min, and then the product was taken out for washing; it was placed in 4% azelaic acid and 0.1% sodium hydroxide by mass percentage, and the current density was 10mA / cm at 80℃. 2 The 3-stage formation was carried out under the conditions of 360V and 8 minutes, and the formation time was controlled at 8 minutes, and the 3-stage formation was carried out under the conditions of 360V and ...360V, and the formation time was controlled at 360V and 8 minutes, and the 3-stage formation was carried out under the conditions of 360V and 360V, and the 3-stage formation time was controlled at 360V and 8 minutes, and the 3-stage formation was carried out under the conditions of 360V and 360V, and the 3-stage formation time was controlled at 360V and 8 minutes, and the 3-stage formation was carried out under the 2The electrode was subjected to four-stage formation at 400 V and 20 min, and then washed with water. The electrode was placed in a 10% by mass concentration of boric acid and a 1% by mass concentration of ammonium pentaborate solution at 80 ° C and a current density of 10 mA / cm 2 , 520V, the formation time is controlled within 5min, and it is taken out for washing; it is immersed in a phosphoric acid solution with a mass percentage concentration of 5%, the temperature is controlled at 50℃, the immersion time is controlled within 5min, and it is taken out for washing; the foil obtained in the above step is placed in an oven, the temperature is controlled at 400℃, and the time is controlled within 3min; it is placed in a boric acid solution with a mass percentage concentration of 4% and an ammonium pentaborate solution with a mass percentage concentration of 0.1%, and it is heated at 80℃ and a current density of 10mA / cm 2 , and the subsequent formation is carried out under the conditions of 520V, the formation time is controlled within 5min, and the foil is taken out for washing to obtain the formed foil;

[0032] (5) Disperse 10 g of SBA-15, 9 g of cellulose and 1 g of methyl cellulose in 150 ml of N-methylpyrrolidone and stir magnetically for 3 min to obtain a mixed solution. Then, place the formed foil in the mixed solution, immerse it for 1 min, take it out, wash it with water, place it in an oven, and dry it at 100 °C to obtain a sandwich structure electrode foil.

[0033] Example 2: A sandwich structure electrode foil, the specific preparation steps are as follows:

[0034] (1) Dissolve 15 g of ammonium fluorotitanate in 1 L of water and stir magnetically for 4 h to obtain an ammonium fluorotitanate solution. Then, 85 μm thick plain foil substrate is immersed in the ammonium fluorotitanate solution and kept at 40 °C for 8 min. After being taken out, it is rinsed with deionized water, drained, and repeated 4 times. Then, it is placed in a muffle furnace at 300 °C for 6 min to obtain a corrosion foil with a 2 nm thick high dielectric constant titanium dioxide film coated on the surface.

[0035] (2) Mix 15 g of aluminum powder with a particle size of 8 μm with 30 ml of ethanol and stir magnetically for 20 min to obtain aluminum powder slurry;

[0036] (3) Use a coating machine to evenly coat the aluminum powder slurry on the upper and lower surfaces of the aluminum foil in step (1), then place it in a muffle furnace, turn on the vacuum pump, and evacuate to 1×10 -2 Pa, sintering was performed, first at a heating rate of 45°C / min to 300°C, kept at that temperature for 6 h, then at a heating rate of 45°C / min to 600°C, kept at that temperature for 10 h;

[0037] (4) The aluminum foil obtained in step (3) was placed in 94°C water and boiled for 9 minutes; then rinsed with deionized water and drained; then placed in 7% by mass concentration of ammonium adipate and 1.5% by mass concentration of ammonium citrate at 80°C and a current density of 15 mA / cm 2 The first stage was formed under the conditions of 150V voltage, the formation time was controlled at 15min, and it was taken out for washing; it was placed in a solution of 6% ammonium adipate and 1.1% ammonium citrate by mass percentage, and the current density was 15mA / cm 2 The secondary formation was carried out under the conditions of 260V and 13min, and the formation time was controlled at 13min, and then the product was taken out for washing; it was placed in 9% azelaic acid and 0.5% sodium hydroxide by mass percentage, and the current density was 15mA / cm at 85℃. 2 The three-stage formation was carried out under the conditions of 360V and 12 minutes, and the formation time was controlled at 12 minutes, and the product was taken out for water washing; it was placed in a solution of 8% azelaic acid and 0.5% sodium hydroxide by mass percentage, and the current density was 15mA / cm at 85℃. 2 The electrode was subjected to four-stage formation at 400 V and 25 min, and then washed with water. The electrode was placed in a boric acid solution with a mass percentage concentration of 11% and an ammonium pentaborate solution with a mass percentage concentration of 1.3%, and heated at 85 °C and a current density of 15 mA / cm 2 , 520V, the formation time is controlled within 6min, and it is taken out for washing; it is immersed in a phosphoric acid solution with a mass percentage concentration of 8%, the temperature is controlled at 70℃, the immersion time is controlled within 7min, and it is taken out for washing; the foil obtained in the above step is placed in an oven, the temperature is controlled at 450℃, and the time is controlled within 4min; it is placed in a boric acid solution with a mass percentage concentration of 12% and an ammonium pentaborate solution with a mass percentage concentration of 0.5%, and it is heated at 85℃ and a current density of 15mA / cm 2 , 520V, the subsequent formation is carried out under the conditions of 8 min, and the formed foil is taken out for washing to obtain the formed foil;

[0038] (5) Disperse 15 g of SBA-15, 15 g of cellulose and 1.5 g of methyl cellulose in 200 ml of N-methylpyrrolidone and stir magnetically for 6 min to obtain a mixed solution. Then, place the formed foil in the mixed solution and immerse it for 2 min. Then, take it out and wash it with water, place it in an oven and dry it at 150 °C to obtain a sandwich structure electrode foil.

[0039] Example 3: A sandwich structure electrode foil, the specific preparation steps are as follows:

[0040] (1) Dissolve 20 g of ammonium fluorotitanate in 1 L of water and stir magnetically for 5 h to obtain an ammonium fluorotitanate solution. Then, 90 μm thick plain foil substrate is immersed in the ammonium fluorotitanate solution and kept at 60 °C for 10 min. After being taken out, it is rinsed with deionized water, drained, and repeated 5 times. Then, it is placed in a muffle furnace at 500 °C for 10 min to obtain a corrosion foil with a 2 nm thick high dielectric constant titanium dioxide film coated on the surface.

[0041] (2) Mix 20 g of aluminum powder with a particle size of 10 μm with 40 ml of ethanol and stir magnetically for 30 min to obtain aluminum powder slurry;

[0042] (3) Use a coating machine to evenly coat the aluminum powder slurry on the upper and lower surfaces of the aluminum foil in step (1), then place it in a muffle furnace, turn on the vacuum pump, and evacuate to 1×10 -2 Pa, sintering was performed, first at a heating rate of 60°C / min to 350°C, kept at that temperature for 8 h, then at a heating rate of 60°C / min to 650°C, kept at that temperature for 12 h;

[0043] (4) The aluminum foil obtained in step (3) was placed in 98°C water and boiled for 10 min; then rinsed with deionized water and drained; then placed in 10% by mass concentration of ammonium adipate and 2% by mass concentration of ammonium citrate at 90°C and a current density of 20 mA / cm 2 The first stage was formed at a voltage of 150 V for 20 min, and the sample was washed with water. The sample was placed in a solution of 10% ammonium adipate and 1.5% ammonium citrate at 90 °C and a current density of 20 mA / cm 2 The secondary formation was carried out under the conditions of 260V and 15 minutes, and the formation time was controlled at 15 minutes, and then the sample was taken out for washing; the sample was placed in a 15% by mass concentration of azelaic acid and a 1% by mass concentration of sodium hydroxide, and the current density was 20 mA / cm at 95°C. 2 The three-stage formation was carried out under the conditions of 360V and 15 minutes, and the formation time was controlled at 15 minutes, and then the product was taken out for washing; it was placed in a 15% by mass concentration of azelaic acid and a 1% by mass concentration of sodium hydroxide solution, and the current density was 20mA / cm at 95℃. 2 The electrode was subjected to four-stage formation at 400 V and 30 min, and then washed with water. The electrode was placed in a 12% by mass concentration of boric acid and a 1.5% by mass concentration of ammonium pentaborate solution at 95 ° C and a current density of 20 mA / cm 2, 520V, the formation time is controlled within 10min, and it is taken out for washing; it is immersed in a phosphoric acid solution with a mass percentage concentration of 10%, the temperature is controlled at 80℃, the immersion time is controlled within 10min, and it is taken out for washing; the foil obtained in the above step is placed in an oven, the temperature is controlled at 550℃, and the time is controlled within 5min; it is placed in a boric acid solution with a mass percentage concentration of 15% and an ammonium pentaborate solution with a mass percentage concentration of 1%, and the current density is 20mA / cm 2 , 520V, the subsequent formation is carried out under the conditions of 10 min, and the formed foil is taken out for washing to obtain the formed foil;

[0044] (5) Disperse 20 g of SBA-15, 18 g of cellulose and 2 g of methyl cellulose in 300 ml of N-methylpyrrolidone and stir magnetically for 10 min to obtain a mixed solution. Then, place the formed foil in the mixed solution and immerse it for 3 min. Then, take it out and wash it with water. Place it in an oven and dry it at 200 °C to obtain a sandwich structure electrode foil.

[0045] Comparative Example 1: A sandwich structure electrode foil, the specific preparation steps are as follows:

[0046] The difference from Example 2 is that methyl cellulose is not contained. The specific steps are as follows:

[0047] (1) Dissolve 15 g of ammonium fluorotitanate in 1 L of water and stir magnetically for 4 h to obtain an ammonium fluorotitanate solution. Then, 85 μm thick plain foil substrate is immersed in the ammonium fluorotitanate solution and kept at 40 °C for 8 min. After being taken out, it is rinsed with deionized water, drained, and repeated 4 times. Then, it is placed in a muffle furnace at 300 °C for 6 min to obtain a corrosion foil with a 2 nm thick high dielectric constant titanium dioxide film coated on the surface.

[0048] (2) Mix 15 g of aluminum powder with a particle size of 8 μm with 30 ml of ethanol and stir magnetically for 20 min to obtain aluminum powder slurry;

[0049] (3) Use a coating machine to evenly coat the aluminum powder slurry on the upper and lower surfaces of the aluminum foil in step (1), then place it in a muffle furnace, turn on the vacuum pump, and evacuate to 1×10 -2 Pa, sintering was performed, first at a heating rate of 45°C / min to 300°C, kept at that temperature for 6 h, then at a heating rate of 45°C / min to 600°C, kept at that temperature for 10 h;

[0050] (4) The aluminum foil obtained in step (3) was placed in 94°C water and boiled for 9 minutes; then rinsed with deionized water and drained; then placed in 7% by mass concentration of ammonium adipate and 1.5% by mass concentration of ammonium citrate at 80°C and a current density of 15 mA / cm 2The first stage was formed under the conditions of 150V voltage, the formation time was controlled at 15min, and it was taken out for washing; it was placed in a solution of 6% ammonium adipate and 1.1% ammonium citrate by mass percentage, and the current density was 15mA / cm 2 The secondary formation was carried out under the conditions of 260V and 13min, and the formation time was controlled at 13min, and then the product was taken out for washing; it was placed in 9% azelaic acid and 0.5% sodium hydroxide by mass percentage, and the current density was 15mA / cm at 85℃. 2 The three-stage formation was carried out under the conditions of 360V and 12 minutes, and the formation time was controlled at 12 minutes, and the product was taken out for water washing; it was placed in a solution of 8% azelaic acid and 0.5% sodium hydroxide by mass percentage, and the current density was 15mA / cm at 85℃. 2 The electrode was subjected to four-stage formation at 400 V and 25 min, and then washed with water. The electrode was placed in a boric acid solution with a mass percentage concentration of 11% and an ammonium pentaborate solution with a mass percentage concentration of 1.3%, and heated at 85 °C and a current density of 15 mA / cm 2 , 520V, the formation time is controlled within 6min, and it is taken out for washing; it is immersed in a phosphoric acid solution with a mass percentage concentration of 8%, the temperature is controlled at 70℃, the immersion time is controlled within 7min, and it is taken out for washing; the foil obtained in the above step is placed in an oven, the temperature is controlled at 450℃, and the time is controlled within 4min; it is placed in a boric acid solution with a mass percentage concentration of 12% and an ammonium pentaborate solution with a mass percentage concentration of 0.5%, and it is heated at 85℃ and a current density of 15mA / cm 2 , 520V, the subsequent formation is carried out under the conditions of 8 min, and the formed foil is taken out for washing to obtain the formed foil;

[0051] (5) Disperse 15 g of SBA-15 and 16.5 g of cellulose in 200 ml of N-methylpyrrolidone and stir magnetically for 6 min to obtain a mixed solution. Then, place the electroplated foil in the mixed solution and immerse it for 2 min. Then, take it out and wash it with water. Place it in an oven and dry it at 150 °C to obtain a sandwich structure electrode foil.

[0052] Comparative Example 2: A sandwich structure electrode foil, the specific preparation steps are as follows:

[0053] The difference from Example 2 is that there is no cellulose and methyl cellulose, and the specific steps are as follows:

[0054] (1) Dissolve 15 g of ammonium fluorotitanate in 1 L of water and stir magnetically for 4 h to obtain an ammonium fluorotitanate solution. Then, 85 μm thick plain foil substrate is immersed in the ammonium fluorotitanate solution and kept at 40 °C for 8 min. After being taken out, it is rinsed with deionized water, drained, and repeated 4 times. Then, it is placed in a muffle furnace at 300 °C for 6 min to obtain a corrosion foil with a 2 nm thick high dielectric constant titanium dioxide film coated on the surface.

[0055] (2) Mix 15 g of aluminum powder with a particle size of 8 μm with 30 ml of ethanol and stir magnetically for 20 min to obtain aluminum powder slurry;

[0056] (3) Use a coating machine to evenly coat the aluminum powder slurry on the upper and lower surfaces of the aluminum foil in step (1), then place it in a muffle furnace, turn on the vacuum pump, and evacuate to 1×10 -2 Pa, sintering was performed, first at a heating rate of 45°C / min to 300°C, kept at that temperature for 6 h, then at a heating rate of 45°C / min to 600°C, kept at that temperature for 10 h;

[0057] (4) The aluminum foil obtained in step (3) was placed in 94°C water and boiled for 9 minutes; then rinsed with deionized water and drained; then placed in 7% by mass concentration of ammonium adipate and 1.5% by mass concentration of ammonium citrate at 80°C and a current density of 15 mA / cm 2 The first stage was formed under the conditions of 150V voltage, the formation time was controlled at 15min, and it was taken out for washing; it was placed in a solution of 6% ammonium adipate and 1.1% ammonium citrate by mass percentage, and the current density was 15mA / cm 2 The secondary formation was carried out under the conditions of 260V and 13min, and the formation time was controlled at 13min, and then the product was taken out for washing; it was placed in 9% azelaic acid and 0.5% sodium hydroxide by mass percentage, and the current density was 15mA / cm at 85℃. 2 The three-stage formation was carried out under the conditions of 360V and 12 minutes, and the formation time was controlled at 12 minutes, and the product was taken out for water washing; it was placed in a solution of 8% azelaic acid and 0.5% sodium hydroxide by mass percentage, and the current density was 15mA / cm at 85℃. 2 The electrode was subjected to four-stage formation at 400 V and 25 min, and then washed with water. The electrode was placed in a boric acid solution with a mass percentage concentration of 11% and an ammonium pentaborate solution with a mass percentage concentration of 1.3%, and heated at 85 °C and a current density of 15 mA / cm 2, 520V, the formation time is controlled within 6min, and it is taken out for washing; it is immersed in a phosphoric acid solution with a mass percentage concentration of 8%, the temperature is controlled at 70℃, the immersion time is controlled within 7min, and it is taken out for washing; the foil obtained in the above step is placed in an oven, the temperature is controlled at 450℃, and the time is controlled within 4min; it is placed in a boric acid solution with a mass percentage concentration of 12% and an ammonium pentaborate solution with a mass percentage concentration of 0.5%, and it is heated at 85℃ and a current density of 15mA / cm 2 , 520V, the subsequent formation is carried out under the conditions of 8 min, and the formed foil is taken out for washing to obtain the formed foil;

[0058] (5) Disperse 15 g of SBA-15 in 200 ml of N-methylpyrrolidone and stir magnetically for 6 min to obtain a mixed solution. Then, place the electroplated foil in the mixed solution and immerse it for 2 min. Then, take it out and wash it with water. Place it in an oven and dry it at 150 °C to obtain a sandwich structure electrode foil.

[0059] Comparative Example 3: A sandwich structure electrode foil, the specific preparation steps are as follows:

[0060] The difference from Example 2 is that there is no molecular sieve, and the specific steps are as follows:

[0061] (1) Dissolve 15 g of ammonium fluorotitanate in 1 L of water and stir magnetically for 4 h to obtain an ammonium fluorotitanate solution. Then, 85 μm thick plain foil substrate is immersed in the ammonium fluorotitanate solution and kept at 40 °C for 8 min. After being taken out, it is rinsed with deionized water, drained, and repeated 4 times. Then, it is placed in a muffle furnace at 300 °C for 6 min to obtain a corrosion foil with a 2 nm thick high dielectric constant titanium dioxide film coated on the surface.

[0062] (2) Mix 15 g of aluminum powder with a particle size of 8 μm with 30 ml of ethanol and stir magnetically for 20 min to obtain aluminum powder slurry;

[0063] (3) Use a coating machine to evenly coat the aluminum powder slurry on the upper and lower surfaces of the aluminum foil in step (1), then place it in a muffle furnace, turn on the vacuum pump, and evacuate to 1×10 -2 Pa, sintering was performed, first at a heating rate of 45°C / min to 300°C, kept at that temperature for 6 h, then at a heating rate of 45°C / min to 600°C, kept at that temperature for 10 h;

[0064] (4) The aluminum foil obtained in step (3) was placed in 94°C water and boiled for 9 minutes; then rinsed with deionized water and drained; then placed in 7% by mass concentration of ammonium adipate and 1.5% by mass concentration of ammonium citrate at 80°C and a current density of 15 mA / cm 2The first stage was formed under the conditions of 150V voltage, the formation time was controlled at 15min, and it was taken out for washing; it was placed in a solution of 6% ammonium adipate and 1.1% ammonium citrate by mass percentage, and the current density was 15mA / cm 2 The secondary formation was carried out under the conditions of 260V and 13min, and the formation time was controlled at 13min, and then the product was taken out for washing; it was placed in 9% azelaic acid and 0.5% sodium hydroxide by mass percentage, and the current density was 15mA / cm at 85℃. 2 The three-stage formation was carried out under the conditions of 360V and 12 minutes, and the formation time was controlled at 12 minutes, and the product was taken out for water washing; it was placed in a solution of 8% azelaic acid and 0.5% sodium hydroxide by mass percentage, and the current density was 15mA / cm at 85℃. 2 The electrode was subjected to four-stage formation at 400 V and 25 min, and then washed with water. The electrode was placed in a boric acid solution with a mass percentage concentration of 11% and an ammonium pentaborate solution with a mass percentage concentration of 1.3%, and heated at 85 °C and a current density of 15 mA / cm 2 , 520V, the formation time is controlled within 6min, and it is taken out for washing; it is immersed in a phosphoric acid solution with a mass percentage concentration of 8%, the temperature is controlled at 70℃, the immersion time is controlled within 7min, and it is taken out for washing; the foil obtained in the above step is placed in an oven, the temperature is controlled at 450℃, and the time is controlled within 4min; it is placed in a boric acid solution with a mass percentage concentration of 12% and an ammonium pentaborate solution with a mass percentage concentration of 0.5%, and it is heated at 85℃ and a current density of 15mA / cm 2 , 520V, the subsequent formation is carried out under the conditions of 8 min, and the formed foil is taken out for washing to obtain the formed foil;

[0065] (5) Disperse 15 g of cellulose and 1.5 g of methyl cellulose in 200 ml of N-methylpyrrolidone and stir magnetically for 6 min to obtain a mixed solution. Then, place the electroplated foil in the mixed solution and immerse it for 2 min. Then, take it out and wash it with water. Place it in an oven and dry it at 150 °C to obtain a sandwich structure electrode foil.

[0066] Comparative Example 4: An electrode foil, the specific preparation steps are as follows:

[0067] (1) Dissolve 15 g of ammonium fluorotitanate in 1 L of water and stir magnetically for 4 h to obtain an ammonium fluorotitanate solution. Then, 85 μm thick plain foil substrate is immersed in the ammonium fluorotitanate solution and kept at 40 °C for 8 min. After being taken out, it is rinsed with deionized water, drained, and repeated 4 times. Then, it is placed in a muffle furnace at 300 °C for 6 min to obtain a corrosion foil with a 2 nm thick high dielectric constant titanium dioxide film coated on the surface.

[0068] (2) Mix 15 g of aluminum powder with a particle size of 8 μm with 30 ml of ethanol and stir magnetically for 20 min to obtain aluminum powder slurry;

[0069] (3) Use a coating machine to evenly coat the aluminum powder slurry on the upper and lower surfaces of the aluminum foil in step (1), then place it in a muffle furnace, turn on the vacuum pump, and evacuate to 1×10 -2 Pa, sintering was performed, first at a heating rate of 45°C / min to 300°C, kept at that temperature for 6 h, then at a heating rate of 45°C / min to 600°C, kept at that temperature for 10 h;

[0070] (4) The aluminum foil obtained in step (3) was placed in 94°C water and boiled for 9 minutes; then rinsed with deionized water and drained; then placed in 7% by mass concentration of ammonium adipate and 1.5% by mass concentration of ammonium citrate at 80°C and a current density of 15 mA / cm 2 The first stage was formed under the conditions of 150V voltage, the formation time was controlled at 15min, and it was taken out for washing; it was placed in a solution of 6% ammonium adipate and 1.1% ammonium citrate by mass percentage, and the current density was 15mA / cm 2 The secondary formation was carried out under the conditions of 260V and 13min, and the formation time was controlled at 13min, and then the product was taken out for washing; it was placed in 9% azelaic acid and 0.5% sodium hydroxide by mass percentage, and the current density was 15mA / cm at 85℃. 2 The three-stage formation was carried out under the conditions of 360V and 12 minutes, and the formation time was controlled at 12 minutes, and the product was taken out for water washing; it was placed in a solution of 8% azelaic acid and 0.5% sodium hydroxide by mass percentage, and the current density was 15mA / cm at 85℃. 2 The electrode was subjected to four-stage formation at 400 V and 25 min, and then washed with water. The electrode was placed in a boric acid solution with a mass percentage concentration of 11% and an ammonium pentaborate solution with a mass percentage concentration of 1.3%, and heated at 85 °C and a current density of 15 mA / cm 2, 520V, the formation time is controlled within 6min, and it is taken out for washing; it is immersed in a phosphoric acid solution with a mass percentage concentration of 8%, the temperature is controlled at 70℃, the immersion time is controlled within 7min, and it is taken out for washing; the foil obtained in the above step is placed in an oven, the temperature is controlled at 450℃, and the time is controlled within 4min; it is placed in a boric acid solution with a mass percentage concentration of 12% and an ammonium pentaborate solution with a mass percentage concentration of 0.5%, and it is heated at 85℃ and a current density of 15mA / cm 2 The subsequent formation is carried out under the conditions of 500V and 520V, the formation time is controlled within 8 min, and the foil is taken out and washed with water to obtain the formed foil.

[0071] Performance Testing

[0072] Specific volume: According to the EIAJ RC-2364A standard method, the specific volume tester is used for measurement. The test results are shown in Table 1.

[0073] Withstand voltage test: Withstand voltage 520Vf, the test solution is 70g / L boric acid, the conductivity is 133.3μs / cm, the pH is 3.2, the sample is immersed in the test solution, the tested part is 6-8mm below the liquid surface, the data is read in the computer of the withstand voltage tester, when it rises to the corresponding withstand voltage value, the corresponding current is the leakage current, the test results are shown in Table 1.

[0074] Hydration resistance: Boil the sample in water for 1 hour, then set the withstand voltage value, and the test system will generate the corresponding voltage rise time and leakage current data.

[0075] Table 1 Performance test results

[0076]

[0077] Data analysis: It can be seen from Examples 1, 2 and 3 in Table 1 that the sandwich structure electrode foil of the present invention has good specific capacitance and low leakage current, and has excellent hydration resistance.

[0078] It can be seen from Example 2 and Comparative Example 1 in Table 1 that the composite film formed by mixing SBA-15, cellulose and methyl cellulose and coating the composite film on the surface of aluminum foil has better hydration resistance. This may be because methyl cellulose is hydrophobic and the composite film contains certain hydrophobic materials, which makes the composite film also have certain hydrophobicity, further improving the hydration resistance of the aluminum foil.

[0079] It can be seen from Example 2 and Comparative Example 2 in Table 1 that the composite film formed by mixing SBA-15 and cellulose and coating the composite film on the surface of the aluminum foil has better hydration resistance. This is mainly because cellulose can form a barrier film, which can better isolate moisture from contacting the aluminum foil compared to the porous structure and adsorption effect of the molecular sieve.

[0080] It can be seen from Example 2 and Comparative Example 3 in Table 1 that the composite film formed by directly mixing cellulose and methyl cellulose and coating them on the surface of aluminum foil has a greatly reduced hydration resistance. This is mainly because when simply forming a composite film on the surface of aluminum foil with cellulose and methyl cellulose, on the one hand, the hydrophilicity and lack of adsorption capacity of cellulose make it easier for water to penetrate into the surface of the aluminum foil. At the same time, the mechanical strength and water-isolating capacity of the composite film will be greatly reduced due to the lack of the porous structure and adsorption effect of the molecular sieve, which affects its hydration resistance. Moreover, when the composite film is soaked in water for a long time, it will be damaged, which will lead to a significant reduction in its hydration resistance.

[0081] It can be seen from Example 2 and Comparative Example 4 that the composite film formed by mixing SBA-15, cellulose and methyl cellulose and coating the composite film on the surface of aluminum foil can isolate a part of moisture from contacting the aluminum foil due to the adsorption and porous structure of the molecular sieve, while cellulose and methyl cellulose can form a composite film on the surface thereof, further isolating the penetration of moisture, and the two have a mutual synergistic effect, which together improves the hydration resistance.

[0082] Those skilled in the art should understand that the discussion of any of the above embodiments is merely illustrative and is not intended to imply that the scope of the present invention is limited to these examples. Under the concept of the present invention, the technical features in the above embodiments or different embodiments may be combined, the steps may be implemented in any order, and there are many other variations of the different aspects of the present invention as described above, which are not provided in detail for the sake of simplicity.

Claims

1. A method for preparing a sandwich structure electrode foil, characterized in that: The following steps are involved: S1: dissolving ammonium fluorotitanate in water to obtain an ammonium fluorotitanate solution, then immersing an aluminum foil in the ammonium fluorotitanate solution, taking out the aluminum foil, cleaning it, and then sintering it; S2: mixing aluminum powder and an organic solvent to obtain aluminum powder slurry, and coating the aluminum powder slurry on the upper and lower surfaces of the aluminum foil obtained in step S1, and sintering to obtain a sintered foil; S3: chemically forming the sintered foil to obtain a chemically formed foil; S4: SBA-15, cellulose, methyl cellulose and N-methyl pyrrolidone are mixed to obtain a mixed solution, and then the formed foil is placed in the mixed solution, washed with water, and dried to obtain a sandwich structure electrode foil; The usage ratio of SBA-15, cellulose, methyl cellulose and N-methyl pyrrolidone in step S4 is 10-20 g: 9-18 g: 1-2 g: 150-300 ml.

2. The method for preparing the sandwich structure electrode foil according to claim 1, characterized in that: During the immersion in step S1, the temperature of the ammonium fluorotitanate solution is 20-60° C., and the immersion time is 6-10 min.

3. The method for preparing the sandwich structure electrode foil according to claim 1, characterized in that: The sintering temperature in step S1 is 200-500° C., and the holding time is 3-10 minutes.

4. The method for preparing a sandwich structure electrode foil according to claim 1, characterized in that: The particle size of the aluminum powder in step S2 is 3-10 μm.

5. The method for preparing a sandwich structure electrode foil according to claim 1, characterized in that: The organic solvent in step S2 is one of ethanol, ethylene glycol, acetone, N-methylpyrrolidone, and N,N-dimethylformamide.

6. The method for preparing a sandwich structure electrode foil according to claim 1, characterized in that: The single-side thickness of the coating in step S2 is 10-30 μm.

7. The method for preparing a sandwich structure electrode foil according to claim 1, characterized in that: The specific process of sintering in step S2 is as follows: -2 Pa, first increase the temperature to 250-350°C at a rate of 30-60°C / min, keep warm for 4-8h, then increase the temperature to 500-650°C at a rate of 30-60°C / min, keep warm for 8-12h.

Citation Information

Patent Citations

  • Aluminum foil capacitor sintered foil and preparation method thereof

    CN118610004A

  • Preparation method of electrode foil with high dielectric constant

    CN114446667A

  • Corrosion-resistant and pollution-resistant molecular sieve coating aluminum foil and preparation method thereof

    CN117165139A